(untitled) (Al-Qamar, 2024)
Dr. Ibrahim is a renowned scholar whose extensive contributions to Arabic and Urdu literature have had a profound impact on the academics and literary researchers of both languages and cultures. After obtaining his foundational education, he pursued higher studies in Urdu at Al Azhar University, followed by advanced degrees from Punjab University, Lahore, where he completed his Master’s and Ph.D. in Urdu language and literature. His books, translations, research papers, articles, lectures and seminars offer new insights and interpretations between Arabic and Urdu. His translations have made significant literary works accessible to a broader audience fostering cross-cultural understanding and appreciation. Arabic being his mother tongue and Urdu learnt and lived at its home - Pakistan, made him arise as an established translator and critic. He won many prestigious awards including ‘Father of Urdu Maulvi Abdul Haq award’ and Pakistan’s national award ‘Tamgha-e-Imtiaz’. Throughout his career, Dr. Ibrahim has been a prolific writer, contributing extensively to both Arabic and Urdu literature. His works reflect a deep understanding and appreciation of both languages, bridging cultural gaps and enriching literary discourse. Dr. Ibrahim’s life and works stand as a testament to his dedication and passion for literature. His contributions continue to inspire and influence scholars and students alike, making him a pivotal figure in the development of Arabic and Urdu literary studies.